Peran Orang Tua dalam Membentuk Karakter Anak sejak Masa Pranatal Sampai Usia 7 Tahun: Kajian Tafsir Tematik Studi Kisah Keluarga Ibrahim dan Keluarga - Ulfah Hajar Munawaroh (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2021)
The purposes of this research are: (1) to discuss the role of parents in shaping the character of children in the perspectives of the Quran and as-sunnah from the pre-natal period to the age of 7; (2) to examines the role of parents in the formation of children's character on the story of the Ibrahim family and the Imran family. This research is library research by using the method of interpretation of theme (thematic). In this research, researcher collecting data from related sources that are primary (Qur'an and hadith), and secondary sources (pole of al-tura>th, parenting books, and journals). Furthermore, the verses and hadiths are reviewed and analyzed to find the meanings contained in the verse and the hadith. The results of this research show that parents have an important role in the formation of children's character, especially at the beginning of their lives. Because the majority of the roles performed by parents at the beginning of their children's lives are fundamental to build child’s character in his future.